The union default solution to declining union membership. (September 2019) - Gall, Gregor; Harcourt, Mark
The continued stasis in the now much reduced aggregate levels of union membership in Britain and elsewhere has such portent for widening inequalities in wealth and power under the neo-liberal variant of late capitalism that a union default requires introduction. In all countries around the world, the de facto system is a non-union default. Under a union default, all workers would be defaulted into membership of the appropriate union. This is not a proposal for compulsory membership, a contravention of individual liberty nor the return of the closed shop by the backdoor because workers will have the right to opt out of membership. The right to be the appropriate default union to which workers would be defaulted into in any workplace would be gained by the union passing a low minimum support threshold. This would bring with it the right to bargain over pay and conditions.